2020
DOI: 10.2147/ott.s246092
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lnc HAGLR Promotes Colon Cancer Progression Through Sponging miR‐185‐5p and Activating CDK4 and CDK6 in vitro and in vivo</p>

Abstract: Background/Aim: LncRNA plays a key role in tumor progression. HAGLR functions as an oncogene in many cancers. However, the molecular mechanism of HAGLR in colon cancer is still unclear. Methods: qRT-PCR was used to measure the expression of HAGLR, miR-185-5p in colon cancer. The expression of CDK4 and CDK6 was detected by Western blot. CCK-8 assay, EdU staining, transwell and Annexin V-FITC/PI assay were used to analyze the effect of HAGLR and miR-185-5p on cell proliferation, invasion, migration and apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…While the expression of HAGLR was upregulated in hepatocellular carcinoma and associated with tumor proliferative and metastatic 25 . Similar ndings in colon cancer and esophageal cancer were reported by Sun and Yang et al 26,27 . Interestingly, HAGLR coordinating with miRNA-19a-3p/TGFBR2 could promote the healing process of a femoral neck fracture.…”
Section: Discussionsupporting
confidence: 89%
“…While the expression of HAGLR was upregulated in hepatocellular carcinoma and associated with tumor proliferative and metastatic 25 . Similar ndings in colon cancer and esophageal cancer were reported by Sun and Yang et al 26,27 . Interestingly, HAGLR coordinating with miRNA-19a-3p/TGFBR2 could promote the healing process of a femoral neck fracture.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the perception of miR-17-5p pathways could help in explaining the mechanisms of principal liver metastases in CRC (15). On the other hand, miR-185-5p and miR-125b-5p appear down-regulated in CRC tissue compared to normal mucosa in other existing studies (52,56). These results are similar to ours, implying that miR-185-5p and miR-125b-5p could bring new information for discriminating and stratifying CRC patients.…”
Section: Discussionsupporting
confidence: 88%
“…MiR-17-5p plays the role of oncomiR in CRC cases ( 50 ), while miR-125b-5p and miR-185-5p act as tumor suppressors ( 51 , 52 ). First, our results from the tissue study indicated that high levels of miR-17-5p in primary CRC could be associated with metastatic potential and serve as a predictive biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Alaiyan et al reported that CCAT1 was gradually upregulated during the progression of CRC and was associated with tumor metastasis [ 17 ]. HAGLR was proved to promote cell growth, migration, and invasion viabilities and inhibit cell apoptosis in CRC [ 18 ]. LncRNA MSC-AS1 is a new lncRNA that has been discovered in recent years, which is first found to be overexpressed in hepatocellular carcinoma tissues [ 19 ].…”
Section: Discussionmentioning
confidence: 99%